2005
DOI: 10.1385/bter:104:3:249
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Nano-TiO<SUB>2</SUB> on the Chloroplast Aging of Spinach Under Light

Abstract: The effects of nano-TiO2 (rutile) on the chloroplast aging of spinach under light were studied. The results showed that when the chloroplasts were illuminated for 1, 5, and 10 min with 500 micromol/cm2/min light intensity, respectively, the evolution oxygen rate was rapidly increased; when the chloroplasts were treated for 20, 30, and 40 min with 500 micromol/cm2/min light intensity, respectively, the evolution oxygen rate was gradually decreased. While spinach was treated with 0.25% nano-TiO2, the rate of evo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(98 citation statements)
references
References 21 publications
3
87
1
Order By: Relevance
“…Addition of 0.25% nano-TiO 2 (rutile) stimulated oxygen evolution rate in spinach chloroplasts, improved chloroplast coupling and enhanced activities of Mg 2+ -ATPase and chloroplast coupling factor I CF 1 -ATPase on the thylakoid membranes [70] and nano-TiO 2 (rutile) protected chloroplasts from aging for long-time illumination [71]. Great increase of the electron transfer, oxygen evolution, and photophosphorylation was observed also in chloroplasts from nanoanatase-TiO 2 -treated spinach under visible light and ultraviolet light illumination [72].…”
Section: Positive Effects Of Mnps On Plantsmentioning
confidence: 99%
“…Addition of 0.25% nano-TiO 2 (rutile) stimulated oxygen evolution rate in spinach chloroplasts, improved chloroplast coupling and enhanced activities of Mg 2+ -ATPase and chloroplast coupling factor I CF 1 -ATPase on the thylakoid membranes [70] and nano-TiO 2 (rutile) protected chloroplasts from aging for long-time illumination [71]. Great increase of the electron transfer, oxygen evolution, and photophosphorylation was observed also in chloroplasts from nanoanatase-TiO 2 -treated spinach under visible light and ultraviolet light illumination [72].…”
Section: Positive Effects Of Mnps On Plantsmentioning
confidence: 99%
“…They found that the mixture of nanoparticles increases nitrate reductase in soybean, increasing its germination and growth. Hong et al 12,13 and Yang et al 14 reported that a proper concentration of nano-TiO 2 was found to improve the growth of spinach by promoting photosynthesis and nitrogen metabolism. Canas et al 15 found that nanofunctionalized carbon nanotubes enhanced root elongation in onion and cucumber.…”
Section: Introductionmentioning
confidence: 99%
“…For example, TiO 2 nanoparticles have been shown to have a toxic effect in vetch, 3 no effect in wheat seedlings, 4 and a positive effect on both photosynthetic rates 5 and chloroplast viability 6 in spinach, although it is unclear how much of this variability is due to the model species tested, the properties of the specific TiO 2 nanomaterials used, and the method of exposure (root vs foliar). Additionally, particle size has been shown B to have large impacts on ENM uptake and distribution patterns in plants, with smaller particles typically being taken up in higher amounts and distributed throughout the plant.…”
mentioning
confidence: 99%